Analysis of combustion phenomena and pollutant formation in a small compression ignition engine fuelled with blended and pure rapeseed methyl ester. (1st July 2016) - Magno, Agnese; Mancaruso, Ezio; Vaglieco, Bianca Maria
Abstract: This paper deals with an investigation on the combustion process and pollutant formation of a small diesel engine fuelled with blended and pure biodiesel. The engine is a three-cylinder, 1028 cc, equipped with a common rail injection system. Endoscope based optical setup was used to observe in the cylinder without significant interference to the combustion process. Combustion images were post-processed by two-colour pyrometry method to evaluate the flame temperature and the in-cylinder soot concentration. Optical data were correlated to the nitrogen oxides and the particulate matter emissions measured at exhaust. Experiments were carried out at different operating conditions. It was found out that without EGR (exhaust gas recirculation), blended and pure RME (rapeseed methyl ester) were characterized by higher flame temperature and also by higher NOx emissions. In presence of EGR, lower flame temperature was detected for biodiesel; in this case higher NOx emissions were measured with biodiesel but the difference with NOx emissions from diesel fuel were reduced. Moreover, blended and pure biodiesel combustion was characterized by lower in-cylinder soot formation and also lower PM (particulate matters) at exhaust. Graphical abstract: Processing of a typical flame image: flame temperature and soot concentration. Highlights: Optical diagnostics are a useful tool to investigate the influence of combustion evolution on the pollutant formation. EGR has a stronger effect on reducing the temperature of biodiesel combustion with respect to diesel fuel. In full load conditions, biodiesel is characterized by lower in-cylinder soot concentration and lower PM at exhaust. Biodiesel combustion produces smaller particles than diesel fuel.